A systematic review of relapse rates during pregnancy and postpartum in patients with relapsing multiple sclerosis - Kerstin Hellwig (SAGE Publishing, 2021)
Introduction: Pregnancy is widely accepted as a period when relapses of multiple sclerosis (MS) are decreased, with an increased risk of relapse in the first months postpartum. This systematic review evaluated relapses during pregnancy and postpartum, according to disease-modifying therapy (DMT) exposure before, during, and after pregnancy, and the influence of DMT on these outcomes. Methods: We searched Medline and EMBASE to identify relevant publications from November 2009 to 2019 along with references lists of selected articles. Publications were filtered and assessed by two independent reviewers to ensure appropriate data extraction. Results: Of 469 articles identified, 28 were included for analysis including 4739 pregnancies in 5324 patients. All five studies comparing natalizumab or fingolimod (high-efficacy DMTs) use preconception versus interferon beta, glatiramer acetate, or dimethyl fumarate, or no DMT suggested that there was a greater risk of relapse during pregnancy following withdrawal of the high-efficacy DMTs. Of 10 studies evaluating relapses during pregnancy, five studies found that continuing DMTs into early pregnancy reduced relapses compared to discontinuing treatment. DMT exposure preconception generally had no effect on postpartum relapses versus no DMT; however, natalizumab or fingolimod use preconception was associated with postpartum relapse versus no high-efficacy DMT in one study. DMT exposure during pregnancy was associated with fewer postpartum relapses versus no DMT exposure in four of seven studies, while three found no difference between groups. Conclusion: Results of this systematic review concerning women with relapsing MS show a complex and often conflicting picture regarding DMT exposure and relapses during and after pregnancy. Although our data are limited by variability between studies, there is some evidence suggesting the use of natalizumab or fingolimod preconception is associated with increased risk of relapses during pregnancy, highlighting the need for effective disease-management strategies in these especially high-risk patients.